Enhancing heritage fruition through 3D virtual models and augmented reality: an application to Roman artefacts - Francesco Gherardini; Mattia Santachiara; Francesco Leali (Virtual Archaeology Review)
The spatial characteristics of museum exhibitions may limit visitors’ experience of the artefacts on display. In the case of large artefacts, limited space may affect their whole visualization, or inhibit the visualization of the details farthest from the observer. In other cases, the storage of artefacts in distant sites (museums or archaeological areas) may influence their knowledge process or the possibility for comparative analysis. Moreover, the precarious state of preservation of some artefacts, with damaged or missing parts, makes it difficult to perceive their original appearance. To overcome these limitations, we propose an integrated approach based on 3D virtual models and Augmented Reality (AR) to enhance the fruition of artefacts, improving their visualization, analysis and personal/shared knowledge, also by overcoming space and time constraints. The final AR application is an easily accessible tool for most users from a mobile device, used both inside and outside museums, opening new perspectives for fruition. The framework encourages the use of free and open source software and standard devices, to maximize their dissemination and exploit the potential of such technologies, which is far greater than current use in the cultural heritage field. Selected case studies to test and validate the integrated framework are proposed, dealing with some Roman artefacts found in the area of Modena (Italy). The first is a Roman floor mosaic, found in Savignano sul Panaro (near Modena) in 2011, of which less than half of its original 4.5 x 6.9 m surface is preserved. The others are two Roman funerary lion sculptures: the first is one of two lions flanking the main door of Modena Cathedral, and the second, well-preserved but damaged, is housed in the Museo Lapidario Estense of Modena. Finally, the application was tested by museum experts and visitors both inside and outside the museum, and positively assessed.